Question
upstudy study bank question image url

Select the correct answer. What is the value of \( a \) in this linear system? \( \begin{array}{l}a-b+c=-6 \\ b-c=5 \\ 2 a-2 c=4 \\ \text { A. } 1 \\ \text { B. }-3 \\ \text { C. } 2 \\ \text { D. }-1\end{array} \)

Ask by Park Perkins. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The value of \( a \) is \( -1 \), which is option D.

Solution

Solve the system of equations \( a-b+c=-6;b-c=5;2a-2c=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}a-b+c=-6\\b-c=5\\2a-2c=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}a=-6+b-c\\b-c=5\\2a-2c=4\end{array}\right.\) - step2: Substitute the value of \(a:\) \(\left\{ \begin{array}{l}b-c=5\\2\left(-6+b-c\right)-2c=4\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}b-c=5\\-12+2b-4c=4\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}b=5+c\\-12+2b-4c=4\end{array}\right.\) - step5: Substitute the value of \(b:\) \(-12+2\left(5+c\right)-4c=4\) - step6: Simplify: \(-2-2c=4\) - step7: Move the constant to the right side: \(-2c=4+2\) - step8: Add the numbers: \(-2c=6\) - step9: Change the signs: \(2c=-6\) - step10: Divide both sides: \(\frac{2c}{2}=\frac{-6}{2}\) - step11: Divide the numbers: \(c=-3\) - step12: Substitute the value of \(c:\) \(b=5-3\) - step13: Simplify: \(b=2\) - step14: Substitute the values of \(b,c:\) \(a=-6+2-\left(-3\right)\) - step15: Simplify: \(a=-1\) - step16: Calculate: \(\left\{ \begin{array}{l}a=-1\\b=2\\c=-3\end{array}\right.\) - step17: Check the solution: \(\left\{ \begin{array}{l}a=-1\\b=2\\c=-3\end{array}\right.\) - step18: Rewrite: \(\left(a,b,c\right) = \left(-1,2,-3\right)\) The solution to the system of equations is \( a = -1 \), \( b = 2 \), and \( c = -3 \). Therefore, the value of \( a \) in this linear system is \( -1 \), which corresponds to option D.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve for \( a \) in the linear system, let's simplify the equations step by step. Starting with the equations: 1. \( a - b + c = -6 \) (Equation 1) 2. \( b - c = 5 \) (Equation 2) can be rewritten as \( b = c + 5 \). 3. \( 2a - 2c = 4 \) (Equation 3) simplifies to \( a - c = 2 \) by dividing everything by 2. Now, we can substitute the expression for \( b \) from Equation 2 into Equation 1: Substituting \( b = c + 5 \) into Equation 1: \[ a - (c + 5) + c = -6 \] This simplifies to: \[ a - 5 = -6 \implies a = -6 + 5 \implies a = -1 \] Therefore, the value of \( a \) is \( -1 \), so the correct answer is \( \text{D. } -1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy